Towards Digital and Efficient MSMEs: The Case of GusMie at Pasar Kayu Jati Rawamangun - Imelda Aprileny; Muhammad Ikhsan; M. Romli; Engkur Engkur; Muhammad Natser (Konsienti : Community Services Journal, 2025)
Micro, Small, and Medium Enterprises (UMKM) in Indonesia often struggle with operational inefficiencies due to manual processes, impacting their growth and competitiveness. GusMie, a noodle and meatball eatery known for its fresh, preservative-free noodles, faces challenges in order duplication, slow financial reconciliation, kitchen workflow bottlenecks, stock mismanagement, and delivery delays. This study proposes integrating a POS system, Kitchen Display System (KDS), and automated inventory management to optimize GusMie's operations. These solutions will ensure more precise tracking of customer orders, improve financial accuracy, streamline kitchen sequencing—especially for its high-demand mie ayam—and enhance stock control to prevent waste of fresh noodles with limited shelf life. Using a case study approach, findings demonstrate that digital transformation significantly improves service speed, order accuracy, stock efficiency, and customer satisfaction, helping GusMie scale sustainably within Indonesia’s competitive food service industry.